Mouse Models of Intracranial Aneurysm. (30th October 2014) - Wang, Yutang; Emeto, Theophilus I.; Lee, James; Marshman, Laurence; Moran, Corey; Seto, Sai‐wang; Golledge, Jonathan
Abstract: Subarachnoid hemorrhage secondary to rupture of an intracranial aneurysm is a highly lethal medical condition. Current management strategies for unruptured intracranial aneurysms involve radiological surveillance and neurosurgical or endovascular interventions. There is no pharmacological treatment available to decrease the risk of aneurysm rupture and subsequent subarachnoid hemorrhage. There is growing interest in the pathogenesis of intracranial aneurysm focused on the development of drug therapies to decrease the incidence of aneurysm rupture. The study of rodent models of intracranial aneurysms has the potential to improve our understanding of intracranial aneurysm development and progression. This review summarizes current mouse models of intact and ruptured intracranial aneurysms and discusses the relevance of these models to human intracranial aneurysms. The article also reviews the importance of these models in investigating the molecular mechanisms involved in the disease. Finally, potential pharmaceutical targets for intracranial aneurysm suggested by previous studies are discussed. Examples of potential drug targets include matrix metalloproteinases, stromal cell‐derived factor‐1, tumor necrosis factor‐α, the renin‐angiotensin system and the β‐estrogen receptor. An agreed clear, precise and reproducible definition of what constitutes an aneurysm in the models would assist in their use to better understand the pathology of intracranial aneurysm and applying findings to patients.